2020
DOI: 10.46300/9106.2020.14.117
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Loan Approval of Bank Direct Marketing Data Using Ensemble Machine Learning Algorithms

Abstract: The Bank Marketing data set at Kaggle is mostly used in predicting if bank clients will subscribe a long-term deposit. We believe that this data set could provide more useful information such as predicting whether a bank client could be approved for a loan. This is a critical choice that has to be made by decision makers at the bank. Building a prediction model for such high-stakes decision does not only require high model prediction accuracy, but also needs a reasonable prediction interpretation. In this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Moreover, by removing redundant features, the model can achieve higher performance [62]. Similar to the findings of this study, Meshref [34], in his study on loan approval prediction, found that feature selection improves the performance of machine learning models rather than using all features. Sarizeybek and Sevli [47] achieved an average performance increase of 7% with the K-Best method in their study on customers' propensity to take loans.…”
Section: Discussion (Tartişma)supporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, by removing redundant features, the model can achieve higher performance [62]. Similar to the findings of this study, Meshref [34], in his study on loan approval prediction, found that feature selection improves the performance of machine learning models rather than using all features. Sarizeybek and Sevli [47] achieved an average performance increase of 7% with the K-Best method in their study on customers' propensity to take loans.…”
Section: Discussion (Tartişma)supporting
confidence: 79%
“…While Meshref [34] notes that the Bank Marketing dataset on Kaggle is often used to predict long-term deposit subscription, he thinks that this dataset can also be used to predict whether loan applications will be approved or not. The research builds a loan approval prediction model using ensemble machine learning techniques such as Bagging and Boosting.…”
Section: Related Research (İlgi̇li̇ Araştirmalar)mentioning
confidence: 99%